Perencanaan Penyediaan Air Bersih Pada Wilayah Rawan Banjir: Studi Kasus: Jl. H. Lamuse Kelurahan Lepo – Lepo Kecamatan Baruga Kota Kendari - Jaya, Wiwi; Sumarlin, Sumarlin; Ndibale, Wa (Universitas Muhammadiyah Kendari, 2022)
The provision of clean water is currently very crucial when entering the rainy season. This is because the occurrence of rainwater affects the turbidity of groundwater and surface water which is usually used for daily needs by the community. Especially in the Lepo-Lepo sub-district area, RT 012-RW 006; RT 013-RW 006, and RT 014-RW 006 are often affected by the high rainy intensity and frequently flooded. So that in this study aims to determine the total clean water consumption for the next 5 years and design a reservoir building for flood victims in the Lepo - Lepo sub-district. The quantitative method is applied by calculating flood-affected communities, projecting clean water consumption, and planning the design of clean water reservoirs. Based on our results, the population projection for flood-affected communities in 2025 is 349 people. Subsequently, the total of clean water consumption for flood victims is 38,400 liters/day which same as the average daily consumption is 6.62 liters/second and the maximum daily use has required of 7.95 liters/second. Moreover, the daily water consumption for high-intensity work is 11.96 liters/second. So we calculated and estimated the reservoir volume is 17.45 m3 with a building length of 4.8 m, a width of 2.4 m., and a height of 1.50 m with the results of 28×14 meters.